2011
DOI: 10.1007/s11357-011-9312-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on islet beta-cell function and its mechanisms in Wistar rats

Abstract: Type 2 diabetes mellitus is characterized by islet β-cell dysfunction and its incidence increases with age. However, the mechanisms underlying the effect of aging on islet β-cell function are not fully understood. We characterized β-cell function in 4-month-old (young), 14-monthold (adult), and 24-month-old (old) male Wistar rats, and found that islet β-cell function decreased gradually with age. Old rats displayed oral glucose intolerance and exhibited a decrease in glucosestimulated insulin release (GSIR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
5
28
0
1
Order By: Relevance
“…In particular, aged mice were insulin-resistant and glucoseintolerant, although intolerance was only observed when aged mice were forced to release more insulin; for example, after a higher glucose load (37,38). Our results concur with those of several previous studies (3,5,6,39) but contrast with studies reporting insulin secretory defects with age (1,2,4,8). The discrepancies in the literature may be explained by the confounding influence of the systemic environment (10).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In particular, aged mice were insulin-resistant and glucoseintolerant, although intolerance was only observed when aged mice were forced to release more insulin; for example, after a higher glucose load (37,38). Our results concur with those of several previous studies (3,5,6,39) but contrast with studies reporting insulin secretory defects with age (1,2,4,8). The discrepancies in the literature may be explained by the confounding influence of the systemic environment (10).…”
Section: Discussionsupporting
confidence: 82%
“…Age-dependent dysfunction of islets and the concomitant dysregulation of blood glucose levels increase the risk for type 2 diabetes (1), which in turn contributes to other age-related chronic diseases. In general, it has been assumed that aging causes an intrinsic dysfunction of the insulin-secreting beta cells through reduced proliferative capacity and/or defective insulin secretion (1)(2)(3)(4)(5)(6)(7)(8)(9). However, there have been numerous reports that age-dependent impairment of glucose homeostasis is not just a result of intrinsic, age-dependent dysfunction of islets but is also caused by systemic factors.…”
mentioning
confidence: 99%
“…In addition, aging might have a significant influence on pancreatic β cell function. Our previous study suggested that β-islet cell function decreased gradually with age (16), and a significant reduction in proliferation and an increase in the frequency of apoptotic β cells were detected in the islets of elderly rats. In a study by Tschen et al (17), the β cell proliferation and the capacity of β cells to regenerate were confirmed to decline with age.…”
Section: Discussionmentioning
confidence: 96%
“…Group I (4M group): 4 months old rats (similar to 14 years of age in humans) [34] without swim exercise training. Group II (4ME group): 4 months old rats (similar to 14 years of age in humans) with swim exercise training for 6 weeks [35] .…”
Section: Experimental Designmentioning
confidence: 99%
“…Group IV (14M-EX group): 14 months old rats (equivalent to 50 years of age in humans) with swim exercise training for 6 weeks [35] . Group V (24M group): 24 months old rats (approximately 84 years of age in humans) [34] without swim exercise training. Group VI (24M-EX group): 24 months old rats (approximately 84 years of age in humans) with swim exercise training for 6 weeks [35] .…”
Section: Experimental Designmentioning
confidence: 99%